1994
DOI: 10.1007/bf01310046
|View full text |Cite
|
Sign up to set email alerts
|

Nucleotide sequences and expression inEscherichia coli of the coat protein genes from two strains of melon necrotic spot virus

Abstract: The nucleotide sequences of coat protein (CP) genes of two Japanese strains of melon necrotic spot virus (MNSV-NH and MNSV-S) were determined. The size of the CP genes of both strains was 1170 nucleotides. Comparisons of the deduced amino acid sequences among MNSV strains showed more than 95% homology, and those among other carmoviruses showed 31-34% homology. cDNAs of MNSV CP genes were cloned into an Escherichia coli expression fusion vector and MNSV-NH and MNSV-S CPs were successfully produced. Furthermore,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1996
1996
2008
2008

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 26 publications
(20 reference statements)
0
1
0
Order By: Relevance
“…AB044292; and MNSV-S, accession no. D29663, Ohshima et al 1994). We found that Ile at position 300 in the MNSV CP corresponded to Leu 294 of the CNV CP and was conserved in all MNSV strains ( Fig.…”
Section: The Mnsv Cp Is Involved In Fungal-vector Transmissionmentioning
confidence: 84%
“…AB044292; and MNSV-S, accession no. D29663, Ohshima et al 1994). We found that Ile at position 300 in the MNSV CP corresponded to Leu 294 of the CNV CP and was conserved in all MNSV strains ( Fig.…”
Section: The Mnsv Cp Is Involved In Fungal-vector Transmissionmentioning
confidence: 84%